BRUGADA SYNDROME-A CASE REPORT - Kuževska-Maneva Konstandina (Sanamed, 2016)
Brugada syndrome is a type of arrhythmia disorder, which is characterised by abnormal electrocardiogram (ECG) findings and an increased risk of sudden cardiac death. The most frequent sign is a persistent ST elevation in the electrocardiographic leads V1-V3 with a right bundle branch block (RBBB).We present a case of 12 years old healthy child, without any complains until then. He had 2 episodes of collapse/syncope, which lasted long and spontaneously disappeared. The collapses were provoked by physical activity. On ECG we found sinus rhythm 62 bpm, RBBB (right bundle brunch block) and Brugada signs in V2 and V3 channel-ST elevation ≥ 2mm. The child was sent in electrophysiological centre abroad where the electrophysiological study was performed. They did not found any accessory pathway. The atrioventricular (AV) conduction was normal. Long lasting polymorphic ventricular tachycardia/fibrillation was induced with programed stimulation with 3 extrastimuli in right ventricular outflow tract. Performing one defibrillation the rhythm turned in sinus way. Then they performed ECG with translocation of electrodes V1-3 in 2nd intercostal space and the Brugada I type findings was discovered. After confirming of presence of Brugada type -1 syndrome the implantable cardioverter- defibrillator (ICD) was applied on child heart.